2018
DOI: 10.1021/acs.inorgchem.8b02271
|View full text |Cite
|
Sign up to set email alerts
|

New Coordination Modes for Modified Schiff Base Ti(IV) Complexes and Their Control over Lactone Ring-Opening Polymerization Activity

Abstract: A series of 8 new bis(alkoxy)bis(phenoxy-imine)titanium(IV) catalysts, coordinated by Schiff base ligands derived from o-vanillin (2-hydroxy-3-methoxybenzaldehyde), show good activity and control for the ring-opening polymerization (ROP) of ε-caprolactone or ω-pentadecalactone. The new complexes are easily prepared in two high-yield steps from commercial reagents. The new ligands can all adopt two different coordination modes, depending on the steric bulk on the imine: a 6-membered NO chelate and/or a 5-member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“… 34 , 44 47 Ti(IV) complexes, coordinated by two ligands and two isopropoxide groups, show coordination-isomer-dependent activities for lactone ROP. 45 First, we tested these Ti(IV) complexes, i.e., [Ti(IV)( o -vanillin schiff base) 2 (OR) 2 ] in epoxide/anhydride ROCOP but they were inactive. Next, a Zr(IV) complex, coordinated by the Schiff base ligand, featuring 2,6-diisopropylphenyl substituents (HL Me ), was targeted.…”
Section: Resultsmentioning
confidence: 99%
“… 34 , 44 47 Ti(IV) complexes, coordinated by two ligands and two isopropoxide groups, show coordination-isomer-dependent activities for lactone ROP. 45 First, we tested these Ti(IV) complexes, i.e., [Ti(IV)( o -vanillin schiff base) 2 (OR) 2 ] in epoxide/anhydride ROCOP but they were inactive. Next, a Zr(IV) complex, coordinated by the Schiff base ligand, featuring 2,6-diisopropylphenyl substituents (HL Me ), was targeted.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been demonstrated that the presence of o-methoxy groups can lead to high activity for lactide ROP for Al(III) salen derivative catalysts. 68 The presence of both monofunctional (chloride, acetate) and bifunctional (CHD) initiating groups in bimodal PDL molar mass distributions in all cases (Fig. S20 †).…”
Section: Polymerization Catalysismentioning
confidence: 92%
“…67 We have also reported bidentate o-vanillin Ti(IV) catalysts, coordinated by two chelating ligands, which showed very high rates in caprolactone ROP (CL ROP, TOF = 1800 h −1 , 0.5 mol%, 80°C). 68 Here, we target the effective tetradentate ortho-vanillin ligand for coordination with metal centres known to catalyse both lactone ROP and epoxide/anhydride ROCOP, i.e. Al(III) and Co(III), to overcome the known limitations of metal salen catalysts in switchable catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium complexes of Schiff-base ligands derived from ortho-vanillin have been recently synthesized by Williams et al (Figure 4) [43]. In this species, each metal center is bound to two Schiff-base moieties and two isopropoxy groups derived from the metal precursor.…”
Section: Runmentioning
confidence: 99%